Parenting Perceptions and Experiences of Healthcare Professionals Employed in Contact Tracing Teams - Figen Gursoy; Ayse Nihal Eraslan; Neslihan Argut; Sena Oz; Damla Cakcak; Mustafa Yavuzekinci; Fikriye Sezer; Selin Ikiz (Anı Publishing, 2023)
The pandemic has mandated some healthcare workers to provide contact tracing services. The present study aimed to discuss the parenting perceptions and experiences of healthcare professionals assigned to contact tracing teams. We carried out this phenomenological study with 29 mothers and 26 fathers selected using the purposive sampling techniques. We collected the data using a demographic information form and a parent interview form and analyzed them using the content analysis method. The results revealed that the parents attempted to balance between the risks of their tasks and their parenting roles. Also, their perception of protecting their families was the basis of their efforts to protect themselves. Moreover, the social distance to family members revealed longing and intimacy expectation among the participants. The pandemic has significantly impacted families, which is exponentially dramatic for contact tracing teams as health workers. Therefore, it seems significant to carry out counseling works with such families.